The glycosylation design space for recombinant lysosomal replacement enzymes produced in CHO cells - Weihua Tian (Nature Portfolio, 2019)
Lysosomal replacement enzymes are taken up by cell surface receptors that recognize glycans, the effects of different glycan features are unknown. Here the authors present a gene engineering screen in CHO cells that allows custom N-glycan-decorated enzymes with improved circulation time and organ distribution.